PERBEDAAN DAYA HAMBAT ANTIBAKTERI ANTARA EKSTRAK DAUN SIRIH MERAH (Piper crocatum) DAN EKSTRAK DAUN SIRIH HIJAU (Piper betle L.) TERHADAP BAKTERI Streptococcus mutans - Risnayanti Anas; Kurniawan Kurniawan; Yustisia Puspitasari (As-Syifaa Jurnal Farmasi, 2018)
Background: Red Betel (Piper crocatum) and green betel (Piper betle L.) is believed to have efficacy preventing dental caries disease caused by the bacterium Streptococcus mutans. Purpose: Research purpose is to review describes different inhibitory  extract of red betel leaf and leaf green betel Against bacteria Streptococcus mutans. Materials and Methods: Operations Research is an experimental  by design post test only group design. Sample Research : is a pure culture of Streptococcus mutans bacteria in the laboratory of Microbiology, Faculty of Pharmacy, University Muslim Indonesia. Analitical statistics to be done using One Way ANOVA. Furthermore, the Post Hoc multiple comparison test for review red betel Differences And green betel  inhibit bacteria. Results: Based on the statistical test showed that the zone of inhibition power of 4 Different the concentration (0.1%, 1%, 10%, 100%) As well as having a significant difference between the two TYPE betel leaf against bacteria Streptococcus mutans. Conclusion: The findings of the data analysis can be concluded that the green betel leaf showed inhibitory better than red betel leaf against bacteria Streptococcus mutans.